A Tofu Wastewater Treatment with A Combination of Anaerobic Baffled Reactor and Activated Sludge System - Wagiman Wagiman; Ag. Suryandono (agriTECH, 2006)
Tofu wastewater contained high organic matters and relatively fluctuated in Chemical Oxygen Demand (COD) of about 5.000 to 8.000 mg/L. A Combination of Anaerobic Baffled Reactor (ABR) and Activated Sludge System was very useful to reduce organic matter and produce higher quality effluent. The continuous operation mode was effective in treating the tofu wastewater at COD below 5.000 mg/L, while efficiency improvement was needed for COD 5.000 mg/L or more. The Batch operation mode might be applied but it should take 11 days hydraulic retention time to match the standard condition. The result also showed that at COD standard point of 100 mg/L, the nitrogen concentration decreased with 80-95 %. The nitrogen removal in the aerobic condition was observed most among other removals, because microorganisms took it as their matrix. In addition, there was an increase in pH from 5,0-6,0 to 7,0 – 7,5 meaning thet there would be an improvement in effluent safety.